Recent Referees (Journal of Political Economy, 2019)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Jonathan AdamsAnna AizerStefania AlbanesiAlberto AlesinaS. Nageeb AliFranklin AllenTreb AllenFernando AlvarezIsaiah AndrewsPeter ArcidiaconoCostas ArkolakisAdrien AuclertChristopher AverySandeep BaligaMarco BassettoBrian BellFrederico BeloDaniel BenjaminDaniel BergstresserJohn BeshearsV BhaskarAndreas BlumeAaron Bodoh-CreedPietro BonaldiAlessandro BonattiLeah BoustanBen BrooksRyan BrownLeonardo BursztynGabriel CarrollSylvain ChassangAndrew ChingGabe Chodorow-ReichJames ChoiCyrus ChuGian ClementiRiccardo ColacitoGeorge ConstantinidesDean CorbaeArnaud CostinotVictor CoutureVincent CrawfordRahul DebMarco Del NegroManasi DeshpandeRebecca DiamondJonathan DingelWill DobbieDavid DornMirko DracaAngela DuckworthPascaline DupasGilles DurantonWioletta DziudaMark EganNatalia FabraHenry FarberJoseph FarrellTimothy FeddersenJoseph FerrieFrederico FinanDoireann FitzgeraldAlexander FrankelCarlos GarrigaMatthew GentzkowRobert GertnerBart GolsteynJoao GomesSanjeev GoyalDavid GreenDaniel GreenwaldNaijia GuoYingni GuoKinda HachemGordon HansonMariaflavia HarariYinghua HeJonas HedlundPaul HeidhuesNathaniel HendrenEmeric HenryHolger HerzStephen HollandPeter IrelandOleg ItskhokiJuanna JoensenLisa KahnMarek KapickaNavin KartikSupreet KaurPatrick KehoeAndreas KleinerPeter KlenowBrian KnightRalph KoijenAnton KolotilinMichael KremerKory KroftNicola LaceteraDavid LagakosRicardo LagosNicolas LambertRasmus LandersoeRobin LeeRaphael LevyWei LiElliot LipnowskiQingmin LiuAlessandro LizzeriMichael LovenheimW. Bentley MacLeodNeale MahoneyIoana MarinescuJames MarroneLaurent MathevetGregor MatvosArnaud MaurelMaurizio MazzoccoTimothy McQuadeXin MengKonrad MenzelKurt MittmanAhmed MobarakJoel MokyrEduardo MoralesStephen MorrisMichael Mueller-SmithCharles NathansonJ. NearyJ. Peter NilssonDmitry OrlovKevin O’RourkeGerard Padro i MiquelFernando ParroEduardo Perez-RichetPetra PerssonSalvatore PiccoloEvan PiermontGiorgio PrimiceriVictoria ProwseCliment Quintana-DomequeJoao RamosJoshua RauhDevesh RavalMorten RavnLuis RayoCullen RobertsKim RuhlJohn RustFlorian ScheuerSam Schulhofer-WohlRajiv SethiJoseph ShapiroCaixia ShenXianwen ShiEran ShmayaAli ShouridehAndrzej SkrzypaczJames SmithAlex SmolinSebastian SoteloCharles SprengerFrancesco SquintaniStefanie StantchevaBryce SteinbergColin StewartTodd StinebricknerPhilipp StrackBalazs SzentesAlan TaylorFelix TintelnotRobert TopelAlexander TorgovitskyAaron TornellSergey TsyplakovMatthew TurnerSelale TuzelPhilip UschevJohannes Van BiesebroeckJohn Van ReenenChristoph VanbergJoseph VavraFrederic VermeulenNicolas VieilleBauke VisserJonathan VogelRakesh VohraHans VothJessica WachterJoel WaldfogelFabian WaldingerChristopher WaltersAndrea WeberPierre-Olivier WeillRonald WolthoffChunhua WuOwen ZidarSeth Zimmerman Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 127, Number 1February 2019 Article DOIhttps://doi.org/10.1086/702873 © 2019 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.